S-PRG-based composites erosive wear resistance and the effect on surrounding enamel - Bergantin, Bianca Tozi Portaluppe; Di Leone, Camilla Cristina Lira; Cruvinel, Thiago; Wang, Linda; Buzalaf, Marília Afonso Rabelo; Borges, Alessandra Buhler [UNESP]; Honório, Heitor Marques; Rios, Daniela (Springer Nature, 2022)
This study evaluated Surface Pre-Reacted Glass-ionomer (S-PRG)-based-composites’ surface resistance against erosive wear and their protective effect on surrounding enamel. Bovine enamel was randomized into 12 groups (n = 10/group) [erosion (e) or erosion + abrasion (a)]: nanohybrid-S-PRG-based composite (SPRGe/SPRGa), nanohybrid-S-PRG-based bulk-fill (SPRGBFe/SPRGBFa), nanoparticle-composite (RCe/RCa), nanohybrid-bulk-fill (BFe/BFa), Glass Hybrid Restorative System (GHRSe/GHRSa), and resin-modified glass-ionomer-cement (RMGICe/RMGICa). Cavities were prepared and restored. Initial profile assessment was performed on material and on adjacent enamel at distances of 100, 200, 300, 600, and 700 μm from margin. Specimens were immersed in citric acid (2 min; 6×/day for 5 days) for erosion. Erosion + abrasion groups were brushed for 1 min after erosion. Final profile assessment was performed. Two-way ANOVA and Tukey-test showed: for erosion, the GHRSe and RMGICe presented greater material wear compared to the other groups (p = 0.001); up to 300 μm away from restoration, GHRSe and SPRGBFe were able to prevent enamel loss compared to RMGICe and other composite groups (p = 0.001). For erosion + abrasion, none of the materials exhibited a significant protective effect and S-PRG-based groups showed lower wear than RMGICa and GHRSa, and higher wear than composites (p = 0.001). S-PRG-based-composites can diminish surrounding enamel loss only against erosion alone, similarly to GIC, with advantage of being a more resistant material.